Determination of the Λ c + spin via the reaction e + e − → Λ c Λ ¯ c - Ablikim, M.; Achasov, M. N.; Adlarson, P.; Ahmed, S.; Albrecht, M.; Aliberti, R.; Amoroso, A.; An, M. R.; An, Q.; Bai, X. H.; Bai, Y.; Bakina, O.; et al. (Physical review. D, 2021)
We report on a comparison of two possible Λ+c spin hypotheses, J = 1/2 and 3/2, via the process e+e− → Λ+ c¯Λ−c , using the angular distributions of Λ+c decays into pK0S , Λπ+, Σ0π+, and Σ+π0. The data were recorded at √ s = 4.6 GeV with the BESIII detector and correspond to an integrated luminosity of 587 pb−1. The Λ+c spin is determined to be J = 1/2, with this value favored over the 3/2 hypothesis with a significance corresponding to more than 6 Gaussian standard deviations.